Early Outpatient Physical Therapy May Improve Range-of-Motion in Primary Total Knee Arthroplasty - McGinn, Tanner; Chughtai, Morad; Khlopas, Anton; Grasmick, Paige; Mullaji, Arun B.; Harwin, Steven F.; Bhave, Anil; Mont, Michael A. (The Journal of Knee Surgery, 2017)
Knee stiffness is a relatively common complication following a primary total knee arthroplasty (TKA). Following this procedure, rehabilitation is essential to maintain, improve, and prevent the loss of knee range-of-motion (ROM). Currently, there is a paucity of studies describing whether the timing of physical therapy (PT) post-TKA plays a role in ROM outcomes. Therefore, the purpose of this study was to compare (1) flexion and (2) extension ROM at final follow-up of TKA patients who either began outpatient physical therapy (OPT) within 6 weeks or after 6 weeks of their TKA. Surgical records from all TKAs performed at one institution (three surgeons) between January 2013 and December 2014 (n = 485) were analyzed. Their mean age was 63 years (range, 32–90 years). Patients were stratified into two cohorts: patients who had OPT within 6 weeks (n = 411) and those who started after 6 weeks (n = 74). The t-tests were used to compare mean flexion and extension ROM at final follow-up. The patients who attended OPT within 6 weeks had a significantly higher mean flexion ROM at their final clinical visit ([mean, 114 degrees; range, 60–140 degrees] versus [mean, 111degrees; range, 80–130 degrees]). There was a lower mean extension in the patients who attended PT earlier as compared with those who attended it later (0.7 vs. 1.5 degrees). Patients who attended OPT within 6 weeks of TKA had a better mean flexion and extension ROM as compared with those who started after 6 weeks. Attending PT earlier may allow a patient to have better ROM and decreased stiffness. Because stiffness recalcitrant to PT is usually treated with manipulation under anesthesia (MUA), attending PT earlier and improving ROM may potentially allow post-TKA patients to avoid undergoing manipulation under anesthesia. Further work is needed to validate these findings. Future studies should be prospective with larger cohorts.
Keywords: total knee replacement; physical therapy; timing; knee arthroplasty